APPLICATION OF THE DMAIC PROCESS IMPROVEMENT METHODOLOGY AS AN INSSTRUMENT FOR INTEGRATED WATER MANAGEMENT - Natalia I. Matova; Tatiana L. Gorbunova; Du Toit J.S (Водное хозяйство России: проблемы, технологии, управление)
A significant part of the Sochi resort region is included into the unique natural protected areas, such as the Caucasus biosphere reserve and Sochi National Park. Development of the regional economy is largely dependent on the natural geo/bio/cenoses management effectiveness on the protected territories. Monitoring of the water resources status and their management is of the particular importance, since the biodiversity of the aquatic environment and the terrestrial flora and fauna of the area dependent on these factors, as well as ensuring the citizen’s requirements and rights. However, presently no one of the existing water environment state assessment methods is able to account various and complex natural communities’ responses to different stress factors and their combined impact. The article presents the world experience on concept of the Integrated Water Resource Management (IWRM) application and development of the some aspect of the comprehensive natural resources regulation methodology. The authors believe that some elements of environmental management practiced in national parks and reserves of the republic of South Africa can be applicable in development of a system that provides consistent monitoring of environmental quality, the mastering of a sufficient and user-friendly database, based on a set of measures for the conservation and restoration of natural resources One of the most significant watercourses of the protected nature territories of the South of Russia, the Mzymta River has been used as a study case.